2015
DOI: 10.1016/j.jfda.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage time on metabolite profile and alpha-glucosidase inhibitory activity of Cosmos caudatus leaves – GCMS based metabolomics approach

Abstract: Cosmos caudatus, which is a commonly consumed vegetable in Malaysia, is locally known as "Ulam Raja". It is a local Malaysian herb traditionally used as a food and medicinal herb to treat several maladies. Its bioactive or nutritional constituents consist of a wide range of metabolites, including glucosinolates, phenolics, amino acids, organic acids, and sugars. However, many of these metabolites are not stable and easily degraded or modified during storage. In order to investigate the metabolomics changes occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 41 publications
5
22
0
Order By: Relevance
“…Steric accessibility is a major determinant for redox reactions with DPPH, where small antioxidants that have better access to the radical site than their larger counterparts tend to have higher DPPH-reducing power [ 42 ]. This finding corroborates previous studies that reported a negative relationship between the IC 50 values of DPPH radical scavenging and GAE [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Steric accessibility is a major determinant for redox reactions with DPPH, where small antioxidants that have better access to the radical site than their larger counterparts tend to have higher DPPH-reducing power [ 42 ]. This finding corroborates previous studies that reported a negative relationship between the IC 50 values of DPPH radical scavenging and GAE [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…The extracts were prepared in six replicates and stored at −80°C prior to further analysis. Each extract was tested for α-glucosidase inhibitory activity and analyzed using GC-MS [ 56 , 57 ].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…One of the therapeutic approaches for diabetes management is to slow down the absorption of postprandial glucose by inhibiting carbohydrate hydrolyzing enzymes, such as α-glucosidase [2]. However, the currently available α-glucosidase inhibitors including acarbose, voglibose and miglitol produce gastrointestinal side effects [3]. Hence, efforts are being made to search for antioxidants and α-glucosidase inhibitors from natural resources for the management of diabetes and its complications.…”
Section: Introductionmentioning
confidence: 99%